Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1007/s12471-012-0346-y
|View full text |Cite
|
Sign up to set email alerts
|

Baroreflex sensitivity: mechanisms and measurement

Abstract: This article is a brief review of baroreflex physiology, the definition and functional meaning of baroreflex sensitivity, and the methods used to measure baroreflex sensitivity. The arterial baroreflex is important for haemodynamic stability and for cardioprotection, and it has convincingly been demonstrated that baroreflex sensitivity, even when assessed with different methods, has a strong prognostic value. Development of new baroreflex assessing procedures is still ongoing, with a focus on increased reliabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
77
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(88 citation statements)
references
References 11 publications
4
77
2
1
Order By: Relevance
“…Neurocardiology refers to (patho)physiological interplays of the nervous and cardiovascular systems [2]. Baroreflex sensitivity and heart rate variability are important parameters in understanding the influence of the autonomic nervous system on both heart and brain activity [3,4]. Over the past years, there is increasing evidence about the brainheart interaction with major potential implications for treatment of cardiovascular diseases.…”
mentioning
confidence: 99%
“…Neurocardiology refers to (patho)physiological interplays of the nervous and cardiovascular systems [2]. Baroreflex sensitivity and heart rate variability are important parameters in understanding the influence of the autonomic nervous system on both heart and brain activity [3,4]. Over the past years, there is increasing evidence about the brainheart interaction with major potential implications for treatment of cardiovascular diseases.…”
mentioning
confidence: 99%
“…In a previous study, we observed reduction of the bradycardic response of infarcted rats submitted to direct vagal stimulation (33), suggesting a possible desensitization of the cholinergic receptors of the heart after infarction. Baroreceptor desensitization may also exert a central role in this process because changes in the afferent information to the central nuclei are important to regulate the sympathetic and vagal tone directed to the entire cardiovascular system (6,19,24). LF power is modulated by the baroreflex thus affecting the sinus node response to BP changes (34).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, maintenance of normal reflexes to adjust BP regulation is important for cardiovascular homeostasis (6). …”
Section: Introductionmentioning
confidence: 99%
“…It also provides insights on the reduction of cognitive functions after major forms of cardiac surgery, on cardiovascular risk factors that affect cognitive functions in the brain [12] and on the effects of exercise training on cardiac and cognitive function [13]. It highlights the importance of the baroreflex in the heart-brain connection [14,15], and potential pathophysiological and molecular mechanisms of the effects of cerebral hypoperfusion and cognitive function [16].…”
mentioning
confidence: 99%